A Case of Hip Disarticulation following Parenteral Narcotic Abuse and Literature Reviews - Ugbeye, Michael Ebiyon; Alatishe, Kehinde Adesola; Olawoye, Olayinka (Nigerian Journal of Orthopaedics and Trauma, 2018)
Pentazocine is one of the commonly prescribed narcotic analgesics for acute pain management such as post‑operative or post‑traumatic pain in developing countries. It has a high potential for abuse due to its euphoric effect. This abuse can lead to cutaneous, vascular, respiratory and central nervous system complications. Vascular complications include pseudoaneurysm formation, deep venous thrombosis, arteriovenous fistula, infected thrombi, arterial embolisation, infective endocarditis and gangrene. However, reports of amputation surgery for vascular complications following pentazocine abuse are few in the literature. We report a case of lower limb gangrene following a chronic abuse of self‑administered injection pentazocine in a 38‑year‑old female who inadvertently ruptured her right femoral artery pseudoaneurysm. She had ligation of the bleeding vessel and an iliofemoral bypass surgery with synthetic polytetrafluoroethylene graft. This salvage procedure failed due to graft thrombosis, and she eventually had a right hip disarticulation.